Demographics of Lagocephalus inermis in the Arabian Sea unveils complex conservation challenges. Issue 1 (27th December 2018) - Anju, Chakkalathara Venu; Dahanukar, Neelesh; Sidharthan, Arya; Ranjeet, Kutty; Raghavan, Rajeev
Abstract : The first assessment of the demographics of Lagocephalus inermis, a species associated with pufferfish bites and fishing down the food web in the Arabian Sea, south‐west coast of India, was performed based on length structured population dynamics of 1601 individuals caught in commercial fisheries. Analysis revealed that the current level of exploitation is 90% of the predicted exploitation producing maximum relative yield per recruit ( E max ), suggesting high levels of exploitation with potential for significant negative consequences for trophic cascades.